The new a-theory of time - Tallant, Jonathan (Taylor and Francis, 2015)
The New A-theory of Time (TNAT) is the view, to be elaborated and defended in this article, that many times exist, and that time is real in virtue of every moment in time bearing each of the so-called A-properties: past, present and future. I argue that TNAT is at least as theoretically virtuous as mainstream views in the philosophy of time and may have some claim to being our best theory of time. I show that the properties ‘past’, ‘present’ and ‘future’ can be understood as compatible intrinsic properties. Having demonstrated that this account of the A-properties is coherent, I go on to demonstrate how TNAT can give us an account of passage, change and the truth-conditions for temporal sentences. In the final section of the article, I develop a tentative argument in favour of TNAT, though concede that we have to settle for the result that TNAT is on a par with our other theories of time. In the remainder of this opening section, my aim is to situate the current proposal as a direct response to McTaggart’s infamous argument against the reality of time.